Analysis of Project-Based Problem-Solving Skills of Optical Equipment Materials with Heller and Heller Steps - Viyanti Viyanti; Rizki Eka Shintya; Undang Rosidin; Agus Suyatna; Noor Farawahidah (Jurnal Pendidikan IPA Indonesia, 2025)
Problem-solving skills are a crucial competency in physics learning, but assessments of optical instrument materials often focus solely on routine tasks and final project results, without incorporating integrated project-based assessment tools. This study aims to analyze students' problem-solving skills using a project-based assessment on optical instrument materials, following the steps outlined by Heller and Heller. This study employed descriptive research with 64 eleventh-grade students as subjects. The assessment instruments were developed based on problem-solving indicators, as outlined by Heller and Heller, including problem focus, problem description, solution planning, plan implementation, and solution evaluation. Data were collected through observation of students' learning activities and analyzed using descriptive statistics in the form of achievement percentages. The study's results demonstrated a high level of validity, as verified by experts, and a high level of practicality, supported by positive responses from students. Problem-solving indicators, including focus on the problem, solution planning, plan implementation, and solution evaluation, achieved an average of 82% (very good category), while the problem description indicator achieved 77% (good category). These findings suggest that project-based assessment tools have potential in supporting the development of students' problem-solving skills, although they need to be strengthened in terms of physically describing problems. This study contributes to the alignment of project-based problem-solving indicators, offering a process-oriented and contextual approach to assessing cognitive skills. Further research is recommended to test the effectiveness of PjBL directly on improving students' problem-solving skills through experimental designs with control groups, as well as the development of more adaptive digital instruments for application in 21st-century physics education.